Anxiety and depressive symptoms during the COVID-19 emergency period: A comparative cross-sectional study in professional football - Gouttebarge, V.; Ahmad, I.; Mountjoy, M.; Rice, S.; Kerkhoffs, G. (Clinical Journal of Sport Medicine, 2022)
Objective: The primary objective of our study was to establish the prevalence of anxiety and depressive symptoms among professional football (ie, soccer; hereinafter "football") players during the COVID-19 emergency period, drawing comparisons with players assessed before exposure to the COVID-19 emergency period. Design: Observational comparative cross-sectional study by means of electronic questionnaire. Setting: Professional football. Participants: A total of 468 female (mean age: 22.8 years) and 1134 male (mean age: 26.0 years) players participated. The non-COVID-19 comparison group consisted of 132 female (mean age: 23.1 years) and 175 male (mean age: 24.8 years) professional footballers. Intervention: N/A. Main Outcome Measures: Anxiety symptoms were measured with the validated Generalized Anxiety Disorder 7 and depressive symptoms with the validated Patient Health Questionnaire 9. Both instruments have been widely used in both clinical and research settings among different populations, showing excellent psychometric properties. Results: During the COVID-19 emergency period, the 2-week prevalence of symptoms consistent with a diagnosis of generalized anxiety disorder and depression was 18.2% and 21.6%, respectively, among female professional footballers and 15.5% and 12.9%, respectively, among male players. The 2-week prevalence of anxiety and depressive symptoms among professional footballers was significantly higher during the COVID-19 emergency period than before the global pandemic (P < 0.01). Differences were most pronounced for those worried about the playing future. Conclusions: The COVID-19 emergency period is associated with increased symptoms of anxiety and depression in professional footballers, especially among those worried about their future as players.